Teaching and research of plasma/fluid mechanics to undergraduate students at a US university. Issue 1 (2nd January 2020) - Goldstein, M.; Huang, Y. M.; Scales, W.; Sen, S.
Abstract : We narrate our experiences of teaching plasma and fluid mechanics to undergraduate students at Bowie State University and Virgin Tech and comment on possible pathways for future improvements in plasma and fluid education in general. The areas mostly covered are fusion energy science and space sciences with major emphasis on numerical and computational aspects. Students also participated in activities at NASA-GSFC.